Penyelenggaraan Pendidikan Formal dan Non Formal dalam Pesantren: Analisis terhadap Pasal 17 UU Nomor 18 Tahun 2019 - Tabibuddin, M.; Mukhlis, Mukhlis; Jamaluddin, Jamaluddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study aims to analyze the implementation of Article 17 of Law Number 18 of 2019 concerning Islamic Boarding Schools (Pesantren), which regulates the provision of formal and non-formal education within the Pesantren environment in Indonesia. Pesantren education plays a crucial role in developing students' character and skills while preserving religious values. However, the presence of new regulations in the form of Law Number 18 of 2019 raises questions about how Pesantren will carry out formal and non-formal education in accordance with the new rules. This research utilizes a literature analysis method to examine various literary sources, including Law Number 18 of 2019, its implementing regulations, as well as empirical studies related to the implementation of Article 17. The study also seeks perspectives from various stakeholders, such as Pesantren leaders, teachers, and the surrounding community, to understand the impacts and challenges faced in conducting formal and non-formal education. The results of this research are expected to provide a better understanding of how Pesantren can comply with legal regulations while continuing education in line with the principles and values inherent in the Pesantren tradition. Furthermore, this study also has the potential to offer recommendations for policy improvements or practical guidelines for Pesantren in conducting effective formal and non-formal education in accordance with applicable rules. Thus, this research is anticipated to contribute to the development of the Pesantren education system in Indonesia and enhance understanding of the role of Pesantren in society.